Motion-Free Super-Resolution - Chaudhuri, Subhasis; Manjunath, Joshi (Springer US : Imprint: Springer, 2005)
With the explosion of Internet technology and graphics engines, digital images are now everywhere. Image capturing tools are all pervading - in our pockets to inside a satellite. And although imaging applications demand an availability to high resolution images, such images are not picture perfect and may be lacking sufficient details. This requires that these images be super-resolved for improved details. How to achieve this is what constitutes research in the area of image super-resolution. Motion-Free Super-Resolution explores new technology for image super-resolution - applying cues other than the motion cue in super-resolving a scene. This book will serve as an essential reference for both academecians and practicing engineers in the area of image processing and computer vision, as well as providing a basis for ongoing research in this field.